ANALISIS KEPUASAN MASYARAKAT TERHADAP LAYANAN LISTRIK PRABAYAR - Nofiana, Iryati Nur (Jurnal Ekonomi Pembangunan, 2011)
The research objective is to find out how much public response to the electrical system of prepaid payment services in PT PLN (Persero) Mojokerto District, to know the standards of good service to the community performed by employees in PT PLN (Persero). Analysis tools used in this study using public indeks and SWOT analysis. Analytical results obtained are the payment service user respondents answer pre-paid electricity system in PT PLN (Persero) Mojokerto District. Based on this research, the implications of this study from all the answers given by respondents to the researcher, that the services provided by PT PLN (Persero) relating to the standards of public service include speed, accuracy, and cost of the prepaid electricity system in a state of very satisfied and deserve to be retained, while for public response to give service quality, respondens expressed very satisfied and deserve to be preserved.